Optimization of glycolipid synthesis in hydrophilic deep eutectic solvents - Hollenbach, R.; Bindereif, B.; Van Der Schaaf, U.S.; Ochsenreither, K.; Syldatk, C. (Karlsruhe, 2020)
Glycolipids are considered an alternative to petrochemically based surfactants because they are non-toxic, biodegradable, and less harmful to the environment while having comparable surface-active properties. They can be produced chemically or enzymatically in organic solvents or in deep eutectic solvents (DES) from renewable resources. DES are non-flammable, non-volatile, biodegradable, and almost non-toxic. Unlike organic solvents, sugars are easily soluble in hydrophilic DES. However, DES are highly viscous systems and restricted mass transfer is likely to be a major limiting factor for their application. Limiting factors for glycolipid synthesis in DES are not generally well understood. Therefore, the influence of external mass transfer, fatty acid concentration, and distribution on initial reaction velocity in two hydrophilic DES (choline:urea and choline:glucose) was investigated. At agitation speeds of and higher than 60 rpm, the viscosity of both DES did not limit external mass transfer. Fatty acid concentration of 0.5 M resulted in highest initial reaction velocity while higher concentrations had negative effects. Fatty acid accessibility was identified as a limiting factor for glycolipid synthesis in hydrophilic DES. Mean droplet sizes of fatty acid-DES emulsions can be significantly decreased by ultrasonic pretreatment resulting in significantly increased initial reaction velocity and yield (from 0.15 ± 0.03 μmol glucose monodecanoate/g DES to 0.57 ± 0.03 μmol/g) in the choline: urea DES. The study clearly indicates that fatty acid accessibility is a limiting factor in enzymatic glycolipid synthesis in DES. Furthermore, it was shown that physical pretreatment of fatty acid-DES emulsions is mandatory to improve the availability of fatty acids.